Physical oceanography from five CTD casts during RV SONNE cruise SO304 - Meng Liu; Alice Lefebvre; Tilmann Schwenk; Volkhard Spieß; Elda Miramontes (PANGAEA, 2025)
Conductivity, temperature and depth (CTD) casts, that also included oxygen and turbidity measurements, were done in three stations: one in the open ocean and two in the submarine canyon. We used a SBE 911 Plus CTD probe, with sensors of conductivity (SBE 4C), temperature (SBE 3plus), pressure (SBE 43), turbidity (Wet Labs ECO) and oxygen (SBE 43). A 300 kHz self-contained Teledyne RD Instruments Workhorse Sentinel ADCP was fixed on the frame of the CTD-Rosette. This setting is called a Lowered Acoustic Doppler Current Profiler (LADCP) and allows to collect full-depth profiles of velocities at stations where the LADCP collects data during CTD-Rosette casts.